2021
DOI: 10.1084/jem.20202084
|View full text |Cite
|
Sign up to set email alerts
|

A high OXPHOS CD8 T cell subset is predictive of immunotherapy resistance in melanoma patients

Abstract: Immune checkpoint inhibitor (ICI) therapy continues to revolutionize melanoma treatment, but only a subset of patients respond. Major efforts are underway to develop minimally invasive predictive assays of ICI response. Using single-cell transcriptomics, we discovered a unique CD8 T cell blood/tumor-shared subpopulation in melanoma patients with high levels of oxidative phosphorylation (OXPHOS), the ectonucleotidases CD38 and CD39, and both exhaustion and cytotoxicity markers. We called this population with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 96 publications
2
46
0
Order By: Relevance
“…Recently, a team has identified in the blood and tumors of melanoma patients a new CD8+ subpopulation with high levels of OXPHOS, strong expression of the ectonucleotidases CD38 and CD39, exhaustion markers and cytotoxicity. A high proportion of this CD8+ subpopulation correlates to immunotherapy resistance [ 98 ] ( Figure 3 ).…”
Section: Lipid Metabolism In Adaptive Immunitymentioning
confidence: 99%
“…Recently, a team has identified in the blood and tumors of melanoma patients a new CD8+ subpopulation with high levels of OXPHOS, strong expression of the ectonucleotidases CD38 and CD39, exhaustion markers and cytotoxicity. A high proportion of this CD8+ subpopulation correlates to immunotherapy resistance [ 98 ] ( Figure 3 ).…”
Section: Lipid Metabolism In Adaptive Immunitymentioning
confidence: 99%
“…Additionally, singlecell transcriptomics was utilized to predict the therapy response in melanoma patients. A CD8 + T cell subpopulation with high levels of oxidative phosphorylation was identified that distinguished immune checkpoint inhibitor responders from non-responders [65]. Similar approaches could be translated to neurology, supporting clinicians in challenging decisions.…”
Section: Disease Monitoring and Clinical Management Of Patients Based...mentioning
confidence: 91%
“…Nevertheless, another study has identified a unique CD8 + T-cell blood/tumor-shared subpopulation in melanoma patients with high levels of oxidative phosphorylation, which is correlated with immune checkpoint inhibitor (ICI) resistance in melanoma patients. The establishment of a transcriptomic profile reflecting CD8 + T cells with high oxidative phosphorylation can be effective in discerning responders from non-responders ( 105 ). The above two studies seem to display contrary conclusions, which might be due to distinct cellular sources of mitochondria in the TME.…”
Section: Mitochondrial Oxidative Phosphorylation In Melanoma Immunologymentioning
confidence: 99%